Psychological differences between south-eastern Australian householders' who intend to leave if threatened by a wildfire and those who intend to stay and defend. (March 2015) - McLennan, J.; Paton, D.; Beatson, R.
Abstract: Disastrous wildfires have occurred often in south-eastern Australia. Following multi-fatality wildfires in Victoria on 7 February 2009 the national approach to community wildfire safety, 'Prepare, stay and defend or leave early', came under intense critical scrutiny. The approach was revised subsequently so as to emphasise leaving as the safest option in the event of a wildfire warning. This study reports findings from a survey of 584 residents of at-risk locations. The majority (47%) reported that they intended to leave if warned of a bushfire threat. However, a substantial minority (24%) reported that they intended to stay and defend their home. A further 29% reported that they intended to wait and see what developed before making a final decision. Those intending to leave differed from those intending to stay and defend in several ways. Those intending to leave were characterised generally by being more concerned about the danger posed by bushfires, they viewed themselves as more vulnerable to bushfire threat and they were worried about their house being destroyed in their absence. Those intending to stay and defend were motivated, mostly, to protect their valued property and they believed that their efforts would be successful. They did not perceive themselves to be risk takers. Those intending to leave generally reported rather low levels of preparations for leaving safely. An appreciable percentage of those intending to stay and defend reported levels of preparations for safe defence which were probably inadequate for safe and effective defence.